Implementasi Supervisi Edukatif Kolaboratif Secara Periodik Dalam Meningkatkan Kinerja Guru - Suyono (Education Reserach Center, 2025)
This study concludes that periodic collaborative educational supervision has a significant impact on improving teachers' performance in various aspects, including lesson planning, teaching execution, and student performance assessment. Through a collaborative approach involving teachers, senior teachers, and supervisors, this research demonstrates that enhancing teachers' performance can be achieved through structured steps and continuous support. The quantitative data obtained supports the findings that teachers have shown improvement in describing learning objectives, managing classrooms, motivating students, and effectively utilizing media and learning resources. The success of this collaborative supervision also lies in the role of the supervisor, who acts not only as an evaluator but also as a colleague who assists and guides teachers in the learning process. This approach creates a more harmonious and supportive relationship, where teachers feel valued and motivated to continue developing their competencies. Through repeated supervision and intensive dialogue, teachers become more confident in implementing modern teaching methods and conducting more varied and in-depth evaluations. The findings of this study align with educational theories that emphasize the importance of a collaborative and supportive supervision approach in developing teacher professionalism. The results are not only relevant to the school studied but also provide practical and theoretical implications that can be adapted by other educational institutions to enhance teaching and learning quality. Therefore, this study recommends the implementation of collaborative educational supervision as an effective strategy for teacher professional development and overall improvement of educational quality. Thus, this study asserts that well-designed and continuous supervision can be a highly effective tool in efforts to improve the quality of education. It is crucial for schools and educational stakeholders to continually strengthen this supervisory approach by providing adequate training, support, and guidance for teachers. This is expected to create a more dynamic, creative, and competitive learning environment, producing graduates who are ready to face the challenges of the modern world